The Treatment of Possible Severe Infection in Infants: An Open Randomized Safety Trial of Parenteral Benzylpenicillin and Gentamicin Versus Ceftriaxone in Infants <60 days of Age in Malawi. Issue 12 (December 2017) - Molyneux, Elizabeth M.; Dube, Queen; Banda, Francis M.; Chiume, Msandeni; Singini, Isaac; Mallewa, Macpherson; Schwalbe, Edward C.; Heyderman, Robert S.
Abstract : Background: The World Health Organization recommends benzylpenicillin and gentamicin as antimicrobial treatment for infants with sepsis in low-income settings, and ceftriaxone or cefotaxime as an alternative. In a meta-analysis from 13 low-income settings, Staphylococcus aureus, Klebsiella spp. and Escherichia coli accounted for 55% of infants with sepsis. In a review of bacterial meningitis, resistance to third generation cephalosporins was >50% of all isolates, and 44% of Gram-negative isolates were gentamicin resistant. However, ceftriaxone may cause neonatal jaundice, and gentamicin may cause deafness. Therefore, we compared parenteral benzylpenicillin plus gentamicin with ceftriaxone as first-line treatment, assessing outcome and adverse events. Methods: This was an open randomized trial carried out in the Queen Elizabeth Central Hospital, Blantyre, Malawi, from 2010 to 2013. Infants <60 days of age with possible severe sepsis received either benzylpenicillin and gentamicin or ceftriaxone. Adverse events and outcomes were recorded until 6 months post discharge. Results: Three-hundred forty-eight infants were included in analyses. Outcome in the benzylpenicillin and gentamicin and ceftriaxone groups was similar; deaths were 13.7% and 16.5% and sequelae were 14.5% and 11.2%, respectively. More infants in the penicillin/gentamicin group required phototherapy: 15% versus 5%, P = 0.03. Thirteen (6%) survivors had bilateral hearing loss. There was no difference between the treatment groups. By 6 months post discharge, 11 more infants had died, and 17 more children were found to have sequelae. Conclusions: Ceftriaxone and gentamicin are safe for infants in our setting. Infants should receive long-term follow-up as many poor outcomes occurred after hospital discharge. Abstract : Supplemental Digital Content is available in the text.